Assembleia mista na recuperação judicial: uma proposta para ampliar a participação na assembleia geral de credores - Leite, Alexandre Borges (2020)
Economic crises have caused an accelerated increase in utilization of the Judicial Recovery Institute. Law 11.101 / 2005 brought news to the insolvency system but only over the years has jurisprudence begun to consolidate the strength and scope of this legislation in the legal scenario, which reaches not only companies in crisis, but also the market, its creditors and guarantors. The general assembly of creditors is the core of this procedure, where creditors, divided in classes, that should be homogeneous, approve or reject judicial recovery plans. These assemblies current format presents features that complicate the effective participation of creditors, especially smaller creditors, when these are forced to deal with facts such as distance, costs, logistics and availability. Creditors absences in these assemblies have an important impact in the quorum, as well as, in the results of the procedure, by leading the companies credits to be more affected by discounts and grace periods applied. Statistical analysis, supported by Jurimery concepts, through a descriptive research on a liable data base of judicial recovery processes, corroborates the low participation of unsecured creditors in deliberation approvals, a certain control of debtors over labor classes, and the micro and small companies, as well as, an effective participation of the more representative creditors in the collateral holders class. Virtual assemblies carried on during the pandemic period demonstrated the high level of attendance. Direct consequences of such format are previous knowledge of the creditors that are able to vote, the possibility to manipulate the quorum, assemblies targeting through sessions suspensions, a greater sacrifice of small creditors, and the approval of plans for irrelevant quantity of creditors. Such aspects imply in a distortion of the institute, reflecting its transparency and credibility. Regardless of legislative reform it is possible to opt for creditors joint assembly, on-site and virtual, of which parts are composed by constructing rules and reestablishing the balance between debtors and creditors. Technology and virtual participation, act in favor of justice access, increasing representativeness, legitimizing decisions that impact the whole society, converging this way with the majority principle. The proposal of the present study has the simple aim to improve the rights